1996
DOI: 10.1021/tx960093r
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Mucochloric and Mucobromic Acids with Adenosine and Cytidine:  Formation of Chloro- and Bromopropenal Derivatives

Abstract: Mucochloric (MCA) and mucobromic acid (MBA)--bacterial mutagens and water disinfection byproducts--were reacted with adenosine, cytidine, and guanosine in N,N-dimethylformamide (DMF). In the MCA reaction with adenosine and cytidine and in the MBA reaction with adenosine one major product was formed. In the reactions of MBA with cytidine and in the reactions of MCA and MBA with guanosine only trace levels of products could be detected, and these were not further characterized. The products from the adenosine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
4
19
0
Order By: Relevance
“…8,10,12 The likely course of the reaction giving rise to the products 5 and 6 is depicted in Scheme 3. Even though the predominance of the cyclic form of 1 under the conditions of the experiment is accepted, 8,12,19 the course of the reaction nevertheless must occur through the open-chain form of 1 8,10,12 with which it is in equilibrium. 19 In the open-chain form, it is the aldehyde carbon that is susceptible to attack by a nucleophile and this course is consistent with labeling experiments performed on analogous reactions.…”
Section: Issn 1424-6376mentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,12 The likely course of the reaction giving rise to the products 5 and 6 is depicted in Scheme 3. Even though the predominance of the cyclic form of 1 under the conditions of the experiment is accepted, 8,12,19 the course of the reaction nevertheless must occur through the open-chain form of 1 8,10,12 with which it is in equilibrium. 19 In the open-chain form, it is the aldehyde carbon that is susceptible to attack by a nucleophile and this course is consistent with labeling experiments performed on analogous reactions.…”
Section: Issn 1424-6376mentioning
confidence: 99%
“…19 In the open-chain form, it is the aldehyde carbon that is susceptible to attack by a nucleophile and this course is consistent with labeling experiments performed on analogous reactions. 8,12 Interestingly, the chlorine in position 3 of MCA (1) is susceptible to net displacement by hydroxide ion to yield mucoxychloric acid (7), 20 another potential electrophile. However, the aldehyde group in the open-chain form of 1 is a powerful electrophile and as such can be expected to be less than discriminating.…”
Section: Issn 1424-6376mentioning
confidence: 99%
“…In vitro studies showed that MBA was able to form adducts with adenosine, to induce positive results in the Ames test, and to induce DNA damage in TK6 cells; nevertheless, it was unable to induce significant increases in the frequency of MN, neither in TK6 cells nor in cultured human lymphocytes [33,48,49]. With respect to MCA (the chlorinated hydroxyfuranone), despite its negative results in the MLA, it was reported as a direct-acting mutagen inducing chromosome damage in mammalian cells and plants, showing a high capacity to induce primary DNA damage (comet assay) in mammalian cells [33,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Mucochloric acid (MCA, 3,4‐dichloro‐5‐hydroxyfuran‐2(5 H )‐one) and mucobromic acid (MBA, 3,4‐dibromo‐5‐hydroxyfuran‐2(5 H )‐one) are two halohydroxyfuranones that have been shown to be direct genotoxins and potential carcinogens 7–14. DNA adducts of mucohalic acids (MXA) are known, with the isolation of etheno, oxalo etheno, and halopropenal derivatives of guanosine, adenosine, and cytosine 15–22…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] DNA adducts of mucohalic acids (MXA) are known, with the isolation of etheno, oxalo etheno, and halopropenal derivatives of guanosine, adenosine, and cytosine. [15][16][17][18][19][20][21][22] In recent years, MXA have also attracted much attention in organic synthesis owing to their high functionalization and availability, and they have been used in the synthesis of heterocycles such as gamma-substituted gamma-butenolides and gamma-lactams, and other furanone derivatives. [23][24][25][26][27][28][29][30][31][32][33][34][35] MXA exist in solution as an equilibrium between two species: [36][37][38][39][40] the cyclic lactone-lactol form ðMXA cl Þ and the openchain aldehyde-acid form ðMXA o op Þ.…”
Section: Introductionmentioning
confidence: 99%